A derivative can be used to describe the rate of change at a single point, or the *instantaneous velocity*. The formula used to calculate the average rate of change looks like this: $$ \dfrac{f(b) - f(a)}{b - a} $$ Interpreting it, this can be described as the change in $y$ over the change in $x$. - Speed is always positive - Velocity is directional As the distance between the two points $a$ and $b$ grow smaller, we get closer and closer to the instantaneous velocity of a point. Limits are suited to describing the behavior of a function as it approaches a point. If we have the coordinate pair $(a, f(a))$, and the value $h$ is the distance between $a$ and another $x$ value, the coordinates of that point can be described as ($(a + h, f(a + h))$. With this info: - The slope of the secant line can be described as $\dfrac{f(a + h) - f(a)}{a + h - a}$, which simplifies to $\dfrac{f(a + h) - f(a)}{h}$. - The slope of the *tangent line* or the *instantaneous velocity* can be found by taking the limit of the above function as the distance ($h$) approaches zero: $$\lim_{h \to 0}\dfrac{f(a + h) - f(a)}{h}$$ The above formula can be used to find the *derivative*. This may also be referred to as the *instantaneous velocity*, or the *instantaneous rate of change*. # Point Slope Formula (Review) $$ y - y_1 = m(x-x_1) $$ Given that $m = f'(a)$ and that $(x_1, y_1) = (a, f(a))$, you get the equation: $$ y - f(a) = f'(a)(x - a) $$ # Line Types ## Secant Line A **Secant Line** connects two points on a graph. A **Tangent Line** represents the rate of change or slope at a single point on the graph. # Notation Given the equation $y = f(x)$, the following are all notations used to represent the derivative of $f$ at $x$: - $f'(x)$ - $\dfrac{d}{dx}f(x)$ - $y'$ - $\dfrac{dy}{dx}$ - $\dfrac{df}{dx}$ - "Derivative of $f$ with respect to $x$" # Functions that are not differentiable at a given point - Where a function is not defined - Where a sharp turn takes place - If the slope of the tangent line is vertical # Higher Order Derivatives - Take the derivative of a derivative # Constant Rule The derivative of a constant is always zero. $$ \dfrac{d}{dx}[c] = 0$$ For example, the derivative of the equation $f(x) = 3$ is $0$. # Derivative of $x$ The derivative of $x$ is one. For example, the derivative of the equation $f(x) = x$ is $1$, and the derivative of the equation $f(x) = 3x$ is $3$. # Exponential Derivative Formula Using the definition of a derivative to determine the derivative of $f(x) = x^n$, where $n$ is any natural number. $$ f'(x) = \lim_{h \to 0} \dfrac{(x + h)^n - x^n}{h} $$ - Using pascal's triangle, we can approximate $(x + h)^n$ ``` 1 1 1 1 2 1 1 3 3 1 1 4 6 4 1 ``` - Where $n = 0$: $(x + h)^0 = 1$ - Where $n = 1$: $(x +h)^1 = 1x + 1h$ - Where $n = 2$: $(x +h)^2 = x^2 + 2xh + h^2$ - Where $n = 3$: $(x + h)^3 = 1x^3h^0 + 3x^2h^1 + 3x^1h^2 + 1x^0h^3 = 1x^3 + 3x^2h + 3xh^2 + 1h^3$ Note that the coefficient follows the associated level of Pascal's Triangle (`1 3 3 1`), and $x$'s power decrements, while $h$'s power increments. The coefficients of each pair will always add up to $n$. Eg, $3 + 0$, $2 + 1$, $1 + 2$, and so on. The **second** term in the polynomial created will have a coefficient of $n$. $$ \dfrac{(x + h)^n - x^n}{h} = \lim_{h \to 0} \dfrac{(x^n + nx^{n-1}h + P_{n3}x^{n-2}h^2 + \cdots + h^n)-x^n}{h} $$ $P$ denotes some coefficient found using Pascal's triangle. $x^n$ cancels out, and then $h$ can be factored out of the binomial series. This leaves us with: $$ \lim_{h \to 0} nx^{n-1} + P_{n3} x^{n-2}*0 \cdots v * 0 $$ The zeros leave us with: $$ f(x) = n, \space f'(x) = nx^{n-1} $$ # Sum and Difference Rules $$ \dfrac{d}{dx}(f(x) \pm g(x)) = f'(x) \pm g'(x) $$ # Product Rule $$ \dfrac{d}{dx} (f(x) * g(x)) = \lim_{h \to 0} \dfrac{f(x +h) * g(x + h) - f(x)g(x)}{h} $$ This is done by adding a value equivalent to zero to the numerator ($f(x + h)g(x) - f(x + h)g(x)$): $$ \dfrac{d}{dx} (f(x) * g(x)) = \lim_{h \to 0} \dfrac{f(x +h) * g(x + h) + f(x + h)g(x) - f(x+h)g(x) - f(x)g(x)}{h} $$ From here you can factor out $f(x + h)$ from the first two terms, and a $g(x)$ from the next two terms. Then break into two different fractions: $$\lim_{h \to 0} \dfrac{f(x + h)}{1} * \dfrac{(g(x + h) - g(x))}{h)} + \dfrac{g(x)}{1} *\dfrac{f(x + h) - f(x)}{h} $$ From here, you can take the limit of each fraction, therefore showing that to find the derivative of two values multiplied together, you can use the formula: $$ \dfrac{d}{dx}(f(x) * g(x)) = f(x) * g'(x) + f'(x)*g(x) $$ # Constant Multiple Rule $$ \dfrac{d}{dx}[c*f(x)] = c * f'(x) $$ # Quotient Rule $$ \dfrac{d}{dx}(\dfrac{f(x)}{g(x)}) = \dfrac{f'(x)g(x) -f(x)g'(x)}{(g(x))^2} $$ # Exponential Rule $$ \dfrac{d}{dx} e^x = e^x $$ $$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$ for all $a > 0$ # Chain Rule $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$ ## Examples > Given the function $(x^2+3)^4$, find the derivative. Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$. 1. First find the derivative of the outside function function ($f(x) = x^4$): $$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$ 2. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$. $$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$ > Apply the chain rule to $x^4$ If we treat the above as a function along the lines of $f(x) = (x)^4$, and $g(x) = x$, then the chain rule can be used like so: $$ 4(x)^3 * (1) $$ # Trig Functions $$ \lim_{x \to 0} \dfrac{\sin x}{x} = 1 $$ $$ \lim_{x \to 0} \dfrac{\cos x - 1}{x} = 0 $$ ## Sine $$ f'(x) = \lim_{h \to 0} \dfrac{\sin(x + h) - sin(x)}{h} $$ Using the sum trig identity, $\sin(x + h)$ can be rewritten as $\sin x \cos h + \cos x \sin h$. This allows us to simplify, ultimately leading to: $$ \dfrac{d}{dx} \sin x = \cos x$$ ## Cosine $$ \dfrac{d}{dx} \cos x = -\sin x $$ ## Tangent $$ \dfrac{d}{dx} \tan x = \sec^2x $$ ## Secant $$ \dfrac{d}{dx} \sec x = \sec x * \tan x $$ ## Cosecant $$ \dfrac{d}{dx} \csc x = -\csc x \cot x $$ ## Cotangent $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$ # Implicit Differentiation - There's a reason differentials are written like a fraction - $\dfrac{d}{dx} x^2 = \dfrac{d(x^2)}{dx}$, or, "the derivative of $x^2$ with respect to $x$" - $\dfrac{d}{dx} x = \dfrac{dx}{dx} = 1$ : The derivative of $x$ with respect to $x$ is one - $\dfrac{d}{dx} y = \dfrac{dy}{dx} = y'$ - Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$. Given these facts: 1. Let $y$ be some function of $x$ 2. $\dfrac{d}{dx} x = 1$ 3. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\ What's the derivative of $y^2$? $\dfrac{d}{dx} y^2 = 2(y)^1 *\dfrac{dy}{dx}$ # Examples > Differentiate $f(x) = 4\sqrt[3]{x} - \dfrac{1}{x^6}$ 4. $f(x) = 4\sqrt[3]{x} = \dfrac{1}{x^6}$ 5. $= 4x^\frac{1}{3} - x^{-6}$ 6. $f'(x) = \dfrac{1}{3} * 4x^{-\frac{2}{3}} -(-6)(x^{-6-1})$ 7. $= 4x^{-2-\frac{2}{3}} + 6x^{-7}$ 8. $= \dfrac{4}{3\sqrt[3]{x^2}} + \dfrac{6}{x^7}$